2010
DOI: 10.1111/j.1440-1630.2009.00814.x
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment and retention issues for occupational therapists in mental health: Balancing the pull and the push

Abstract: The results supported the development of a 'push and pull' conceptualization of recruitment and retention issues, including job-related (intrinsic) and non-job-related (extrinsic) issues. This conceptualization allows organisations to closely examine factors that attract practitioners to positions and those that support or damage staff tenure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(89 citation statements)
references
References 19 publications
3
85
1
Order By: Relevance
“…These findings support the empirical literature in signaling that strategies that reduce professional isolation and increase supports through mechanisms (including clinical supervision), are important for retaining allied health staff (Lloyd & King, 2001;Scanlan et al, 2010;Stagnitti, Schoo, Dunbar, & Reid, 2006).…”
Section: Research Questionsupporting
confidence: 72%
See 2 more Smart Citations
“…These findings support the empirical literature in signaling that strategies that reduce professional isolation and increase supports through mechanisms (including clinical supervision), are important for retaining allied health staff (Lloyd & King, 2001;Scanlan et al, 2010;Stagnitti, Schoo, Dunbar, & Reid, 2006).…”
Section: Research Questionsupporting
confidence: 72%
“…Lack of professional support can negatively affect job satisfaction (Smith, Fisher, Kearne, & Lincoln, 2011), and is consistently associated with intention to leave (Belbin, 2011). Insufficient professional support, such as clinical supervision, is frequently cited as a major reason that health care workers leave their place of employment (Humphreys, Jones, Jones, & Mara, 2002;Scanlan et al, 2010). Studies suggest that health employers who fail to provide their employees with access to professional support are likely to have higher numbers of employees with intent to leave than they would otherwise (Alkorashy & Baddar, 2016;Allan & Ledwith, 1998).…”
Section: Effectiveness Of Clinical Supervision and Intention To Leavementioning
confidence: 99%
See 1 more Smart Citation
“…These results indicate that keeping occupational therapists stimulated is central to maintaining job satisfaction. Although reasons for leaving previous positions were not explored in this study, a previous study indicated that 'feeling bored or stale' was a key reason why occupational therapists left positions (Scanlan et al, 2010).…”
Section: Discussionmentioning
confidence: 97%
“…The antecedents of retention may be different to those of turnover and so future research could compare the attitudinal mechanisms of retention and turnover. We would expect that the antecedents of retention are likely to be 'pull' factors, such as positive experiences and job resources, whereas the antecedents of turnover are likely to be 'push' factors, such as negative experiences and excessive job demands (Scanlan, Still, Stewart and Croaker, 2010). …”
mentioning
confidence: 99%